2013
DOI: 10.1111/1469-0691.12165
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors and impact on long-term pancreatic function of infection following pancreas-kidney transplantation

Abstract: Limited information exists about epidemiology and risk factors of infection following pancreas-kidney transplantation and its impact on long-term pancreatic graft function. A retrospective chart review of episodes of severe infection in consecutive pancreas-kidney transplantations in a single institution was performed to assess the epidemiology, risk factors for infection and their impact on the development of pancreatic graft dysfunction. Ninety-four (81%) of 116 recipients (median follow-up of 1492 days; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…We also found that urinary tract infection was the most frequent infection type, followed by abdominal and surgical site infection. These results are also consistent with those of other studies but not with the study by Herrero‐Martínez et al who reported that surgical site infection was the most frequent in the first month after transplantation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that urinary tract infection was the most frequent infection type, followed by abdominal and surgical site infection. These results are also consistent with those of other studies but not with the study by Herrero‐Martínez et al who reported that surgical site infection was the most frequent in the first month after transplantation.…”
Section: Discussionsupporting
confidence: 92%
“…In this large cohort of adult pancreas transplant recipients, we found that infections were common and clinically relevant to outcomes after transplantation, especially in the early postoperative period. Consistent with other studies reporting a proportion of patients affected by bacterial infections ranging from 51% to 95%, we found that the incidence was 61%. Importantly, our data are supported by our comprehensive analysis of the foci, risk factors, and impact of infection on graft loss.…”
Section: Discussionsupporting
confidence: 92%
“…Our present series of SPKTs shows homogeneity with respect to the distribution of donor, recipient, and perioperative variables between the groups, and intra‐abdominal infections, thrombosis, pancreatitis, bleeding, and leak of the pancreas graft are the most frequent surgical complications after SPKT. Overall infection rate after SPKT has been reported in up to 80% of patients, whereas intra‐abdominal infections can represent up to 70% of all infections after pancreas transplant and are associated with higher risk of mortality and pancreas graft loss . Ninety percent of patients who suffer severe intra‐abdominal infections will need a relaparotomy, and 70% of these will require a pancreas explant .…”
Section: Discussionmentioning
confidence: 99%
“…In pancreas transplant patients, secondary peritonitis is usually associated with anastomotic leaks or pancreas fistulae. Infection with bacteria in general and specifically surgical‐site bacterial infection occurs mainly within the first month of transplantation but bacterial peritonitis after pancreas transplantation may occur later, due to the development of late anastomotic leaks . Usually, secondary peritonitis after pancreas, liver or intestinal transplantation is cured after surgical repair of the anatomical site of the infection and with appropriate antimicrobial therapy.…”
Section: Common Difficult‐to‐treat Bacterial Infections Associated Wimentioning
confidence: 99%